2011
DOI: 10.1007/s11033-011-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of genetic polymorphisms in the carbonic anhydrase VI gene exon 2 and salivary parameters in type 2 diabetic patients and healthy adults

Abstract: The aim of this study was to investigate carbonic anhydrase (CA) VI Exon 2 single nucleotide polymorphism (SNP) and its possible association with salivary parameters in type 2 diabetic patients compared to healthy adults. Caries status was measured by using the DMFT (number of decayed, missing, and filled teeth) index. Unstimulated whole saliva and blood samples were taken. SNPs of CA gene exon 2 were determined by PCR and DNA sequencing. Salivary CA activity and buffering capacity were determined by the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Many investigators have reported that the salivary pH is lower in adults and adolescents with diabetes than it is in healthy adults and adolescents [ 34 36 ]. Reported differences are of sufficient magnitude to be measured by pH paper [ 37 , 38 ], and to have been proposed as a simple screening measure for detection of metabolic syndrome or diabetes [ 39 ]. Therefore, according to our model, blood hyperglycemia in patients with T2D will lead to elevated levels of salivary glucose concentration, an increased synthesis of acidic metabolites by oral acidogenic bacteria, and salivary acidification ( Fig 3 , Point 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that the salivary pH is lower in adults and adolescents with diabetes than it is in healthy adults and adolescents [ 34 36 ]. Reported differences are of sufficient magnitude to be measured by pH paper [ 37 , 38 ], and to have been proposed as a simple screening measure for detection of metabolic syndrome or diabetes [ 39 ]. Therefore, according to our model, blood hyperglycemia in patients with T2D will lead to elevated levels of salivary glucose concentration, an increased synthesis of acidic metabolites by oral acidogenic bacteria, and salivary acidification ( Fig 3 , Point 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mucins and proline-rich proteins take part in bacteria cell agglutination, including cariogenic bacteria [Darshana et al, 2014;Opal et al, 2015]. Researchers examined SNP in genes encoding salivary components -CA6 (for carbonic anhydrase 6), MUC 7 (for mucin), AQP (for aquaporin), and PRH1 (for prolinerich protein 1) [Peres et al, 2010;Yarat et al, 2011;Buczkowska-Radlińska et al, 2012;Koç Öztürk et al, 2012;Wang et al, 2012b;Li et al, 2015;Yildiz et al, 2016]. The relation of the CA6 gene with the buffer capacity of saliva was observed by Yildiz et al [2016] and Peres et al [2010].…”
Section: Discussionmentioning
confidence: 99%
“…However, a later study including 245 children investigated the same 2 SNPs and reported that 1 SNP [rs2274327 (C/T)] was associated with a decrease in salivary buffering capacity in healthy children, but that the gene polymorphisms were not directly related to caries (Peres et al, 2010). Recently, 4 SNPs [rs2274327(C/T), rs2274328 (A/C), rs2274329 (G/C), and rs2274330 (G/C)] were studied in 43 subjects, and no correlation was found between SNPs in CA VI exon 2 and salivary buffering capacity or pH; however, a positive significant correlation was found between salivary CA activity and the frequency of SNPs in exon 2 of CA VI in diabetic groups (Koç et al, 2012). A recent study showed that individuals with the TT genotype (rs2274327) had significantly lower CA VI concentrations than individuals with genotypes CT or CC (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Peres et al, 2010;Padiglia et al, 2010;Koç et al, 2012) examining CA VI gene polymorphisms mainly focused on exon 2 or 3, as these polymorphisms result in changes in the amino acid sequence in the secreted protein and may interfere with enzyme function. However, the introns may be involved in the regulation of gene expression, but no studies have examined the relationship between polymorphisms in the intron regions of the CA VI gene and caries susceptibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation